Coa: Glottopolitics and Criminal Anthropology in Julio Vicuña Cifuentes (1910) - Rojas, Darío (2020)
In this paper we analyze the work Coa: jerga de los delincuentes chilenos. Estudio y vocabulario (1910) by Julio Vicuña Cifuentes, from a glottopolitical approach. We maintain that the ideological representation of the speech of Chilean criminals (coa) contained in said work responds to iconization, through which the criminal policy of the Chilean State is legitimized based on the scientific verification of the alleged degenerate condition of the criminals, reflected in their language. This semiotic strategy has the glottopolitical effect of naturalizing the dominant position of the Chilean socio-economic elites. This representation responds to the Chilean context of the early twentieth century, marked by the emergence of the “cuestión social” and illustrated positivism that marked the institutionalization of anthropological and linguistic studies in Chile during that period.